Iron Based Catalysts Used in Water Treatment Assisted by Ultrasound: A Mini Review - Zhang, Nan; Xian, Guang; Li, Xuemei; Zhang, Panyue; Zhang, Guangming; Zhu, Jia (Frontiers in Chemistry, 2018)
The characteristics and performances of catalyst are the key in catalytic ultrasonic treatment of wastewater, and iron based catalysts are known for low cost, high accessibility and safety. This paper reviewed the current research status of iron-based catalysts in water treatment assisted by ultrasound. Zero valent iron, Fe3O4 and iron composited with other metals were analyzed, their behaviors in catalytic sonochemistry were summarized, and the potential catalytic mechanisms were discussed in details. Finally, the future development in this field was proposed.